The impact of COVID-19 on the mental and sexual health of patients with infertility: a prospective before-and-after study - Jing Qi; Meng Sun; Xingchen Yue; Xintong Hong; Meng Dong; Jichun Tan (BMC, 2024)
Abstract Background The coronavirus disease (COVID-19) pandemic has seriously impacted the mental and sexual health of the general population. Patients dealing with infertility constitute a unique subset within society, susceptible to heightened sensitivity amid pressures and crises. However, to the best of our knowledge, the impact of the different stages of the COVID-19 pandemic on the mental and sexual health of patients with infertility has not been investigated. Therefore, this study aimed to investigate the mental and sexual health of patients with infertility during different stages of the COVID-19 pandemic (during the lockdown, when controls were fully liberalized, and during the post-pandemic era). Methods This prospective before-and-after study was conducted between April and May 2022 (during the lockdown), December and January 2023 (when controls were fully liberalized), and May and August 2023 (during the post-pandemic era). This study explored the sexual and mental health of women with infertility during the three stages of the COVID-19 pandemic using standardized mental health and sexual function questionnaires. The Chi-square test was used to compare categorical data, and the ANOVA test was used to compare numerical data. Results Patients had the highest 7-item Generalized Anxiety Disorder Scale (GAD-7) and 9-item Patient Health Questionnaire (PHQ-9) scores and the highest rates of anxiety and depression during the immediate full-release phase. During the complete liberalization phase, patients had the lowest Female Sexual Function Index (FSFI) scores and the highest incidence of sexual dysfunction. Conclusion This study is the first one to report the repercussions of COVID-19 on the mental and sexual well-being of individuals experiencing infertility across various phases of the pandemic. Upon the complete lifting of control measures, close to 99% of participants exhibited varying degrees of anxiety and depression. Our research underscores that individuals with infertility faced elevated levels of anxiety, depression, and sexual dysfunction during the phase of full liberalization of COVID-19 control measures, in stark contrast to the periods of lockdown and the post-pandemic era.